Digital economy, technology, and urban carbon emissions nexus: an investigation using the threshold effects and mediation effects tests - Sun, Pengsheng; Nisar, Ubair; Qiao, Zhiyuan; Ahmad, Shadab; Kathuria, Khyati; Al Bahir, Areej; Ahmad, Mahmood (Frontiers in Environmental Science, 2024)
IntroductionThis study aims to explore the mechanisms by which the digital economy influences urban carbon emissions in China, with a particular focus on potential threshold effects and the mediating role of technology. As the digital economy grows, it impacts various environmental metrics, including carbon emissions, necessitating a deeper understanding of its nonlinear dynamics and implications for sustainable urban development.MethodsUsing panel data from 286 prefecture-level cities in China spanning from 2012 to 2021, we apply threshold effect models and mediation effect tests. The threshold effect model is employed to investigate non-linear characteristics of the digital economy’s impact on carbon emissions, while the mediation effect model assesses the role of technology as an intermediary in this relationship.ResultsThe threshold effect model reveals a single threshold in the impact of the digital economy on urban carbon emissions, indicating a nonlinear relationship. Initially, the influence of the digital economy on emissions is weak, but as the digital economy develops, its effect becomes more pronounced. The mediation effect model demonstrates that technological advancement can offset the increase in emissions associated with digital economic growth, thus showcasing technology’s potential to mitigate environmental impacts.DiscussionThe findings suggest that while the digital economy generally promotes urban carbon emissions, its impact is non-linear and mitigatable through technological innovation. To curb emissions in urban areas, fostering technological innovation and supporting green technology research and development are critical. Moreover, enhancing management and supervision within the digital economy sector can contribute to balancing economic growth with environmental goals. These insights are valuable for policymakers striving to harmonize digital economic expansion with sustainable environmental practices.